Temperature-dependent Development, Survival, and Oviposition of Laricobius osakensis (Coleoptera: Derodontidae): A Specialist Predator of Adelges tsugae (Hemiptera: Adelgidae). Issue 4 (15th July 2022) - Foley, Jeremiah R; McAvoy, Thomas J; Saint-Amant, Rémi; Régnière, Jacques; Biggs, Abby; Wright, Erika; Mayfield, Albert E; Brewster, Carlyle; Salom, Scott M
Abstract: A predator, Laricobius osakensis Montgomery and Shiyake (Coleoptera: Derodontidae), is being mass-produced and released for the biological control of the invasive hemlock woolly adelgid (HWA), Adelges tsugae Annand (Hemiptera: Adelgidae). To better understand and predict the seasonality of this predator in North America, the development and reproduction of L. osakensis were evaluated at constant temperatures ranging from 5 to 22°C. The predicted seasonal biology was compared with data from field collections. L. osakensis did not complete development from egg to adult at the two lowest temperatures tested, 5 and 8°C, but did so at the highest temperature of 22°C. The minimum development thresholds were estimated for eggs (4.2°C), first (1.8°C), second (5.5°C), third (4.6°C), and fourth instar (4.1°C), prepupa (3.6°C), and pupa (7.5°C). Oviposition rates were significantly greater at 5 and 10°C than at 20 and 25°C. Head capsule width significantly increased for each of the four larval instars with a mean of 0.19, 0.26, 0.35, and 0.44 mm, respectively. Laboratory and field data were used to develop a phenology forecasting model to predict the occurrence of all developmental stages of L . osakensis . This model will allow land managers to more accurately predict the optimal timing for L. osakensis larval sampling throughout its established range.